The tadpole of the hylid frog Scinax belloni (Anura: Hylidae) - Silva-Soares, Thiago; Costa, Paulo Nogueira; Ferreira, Rodrigo B.; Weber, Luiz Norberto (Zootaxa, 2010)
Scinax perpusillus group is composed by11 species. Only Scinax arduous, Scinax littoreus, Scinax. meloi, S. perpusillus, S. tupinamba, and S. v-signatus, have its tadpole described. Herein we described the tadpole of Scinax belloni and its internal oral features. Tadpoles of S. belloni were collected in bromeliads at the Parque Estadual do Forno Grande, municipality of Castelo, Espírito Santo, southeastern. Two tadpoles were reared to froglets in order to allow specific identification. The morphology of S. belloni tadpoles resemble the other known larvae in many aspects such as oval body in dorsal view, coloration, rounded snout in dorsal view, dorsolateral eyes, anteroventral mouth and labial tooth row formula 2(2)/3. In fact, at first sight, all known tadpoles are very similar from each other. Nevertheless, they do can be distinguished by some characters as the shape of lower jaw; number of row of labial papillae; the size of the fins; height of tail and the body; whether musculature of tail reaches its tip and if tail ends rounded or pointed. S. belloni tadpoles are readily differentiated from the other known Scinax gr. perpusillus species tadpoles by the presence of a dark band that goes along the dorsal and ventral fin. The internal oral morphology of S. belloni is also described.